INTRAPRENEURSHIP IN PUBLIC ORGANIZATIONS AS A MECHANISM FOR GENERATING VALUE: A LITERATURE REVIEW - de Santana, Paulo Roberto Peixôto Lima; Pinheiro, Alexandre Santos (Seven Editora, 2024)
This study examined how the principles of entrepreneurship can promote intrapreneurial behavior in the public sector, analyzing the impact of these practices on the innovation and efficiency of public organizations. The main objective was to investigate how entrepreneurial ideals can be integrated into the public environment to improve the quality of services provided to the population. The results indicate that intrapreneurship can transform the public sector by encouraging a more innovative and proactive mindset among employees. The adoption of entrepreneurial practices within public organizations can lead to the reevaluation and improvement of processes and services, resulting in greater efficiency and effectiveness in public management. The study reveals that creating a culture of innovation, where creativity and initiative are valued, can help overcome bureaucratic rigidities and increase employee engagement. Finally, the application of entrepreneurial methods can also improve public perception of the administration, strengthening community trust and support for government initiatives. In summary, intrapreneurship offers a promising path for continuous improvement and innovation in the public sector. DOI:https://doi.org/10.56238/sevened2024.037-109